Predicting cardiovascular risk using a novel risk score in young and middle-age adults with HIV: associations with biomarkers and carotid atherosclerotic plaque. (February 2022) - Rodriguez, Violeta J; Abbamonte, John M; Parrish, Manasi S; Jones, Deborah L; Weiss, Stephen; Pallikkuth, Suresh; Toborek, Michal; Alcaide, Maria L; Jayaweera, Dushyantha; Pahwa, Savita; Rundek, Tatjana; Hurwitz, Barry E; et al.
Background: Traditional risk factors associated with cardiovascular disease (CVD) include older age, smoking, poor diet, lack of exercise, obesity, high blood pressure, high cholesterol, and family history. Young-to-middle age adults (YMAA) are less often identified as being at risk of CVD, but traditional risk scores primarily target older adults and do not accurately estimate risk among YMAA. Methods: This study examined biomarkers associated with CVD risk in YMAA in the context of HIV and cocaine use; risk was assessed by two methods: (1) a relative cardiovascular (CV) risk score that includes several factors and (2) carotid atherosclerotic plaque. Associations between CVD risk (CV risk score and carotid atherosclerotic plaque) and proinflammatory cytokines, markers of immune activation, HIV status, and cocaine use were examined. Participants ( N = 506) included people with and without HIV and people who use or do not use cocaine. Results: Participants' mean age was 36 (SD = 9.53); half (51%) were men. Cocaine use and C-reactive protein were associated with greater relative CV risk scores, but no associations between biomarkers and CV risk emerged. Age and CV risk scores were associated with carotid atherosclerotic plaque, but biomarkers were not. HIV was not associated with CV risk scores or carotid atherosclerotic plaque. Conclusions: Among YMAA, CV risk scores may help providers identify lifestyle changes needed among those at risk for CVD before more advanced risk (e.g., atherosclerotic plaque) is identified. Implications are discussed.